DOI: 10.29007/kzk1
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Analyzer: A Sentiment Analysis Using Social Media Data

Abstract: The usage of social media is rapidly increasing day by day. The impact of societal changes is bending towards the peoples’ opinions shared on social media. Twitter has re- ceived much attention because of its real-time nature. We investigate recent social changes in MeToo movement by developing Socio-Analyzer. We used our four-phase approach to implement Socio-Analyzer. A total of 393,869 static and stream data is collected from the data world website and analyzed using a classifier. The classifier identify an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…2) Labeling: In order to annotate the data set, we followed guidelines by Bandi and Fellah [4] and labeled each tweet as positive, negative, or neutral. The TextBlob tool 3 was used for the purpose of labeling the emotional sentiment into positive, negative, and neutral.…”
Section: A Covidsenti Data Collection and Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Labeling: In order to annotate the data set, we followed guidelines by Bandi and Fellah [4] and labeled each tweet as positive, negative, or neutral. The TextBlob tool 3 was used for the purpose of labeling the emotional sentiment into positive, negative, and neutral.…”
Section: A Covidsenti Data Collection and Labelingmentioning
confidence: 99%
“…The TextBlob tool 3 was used for the purpose of labeling the emotional sentiment into positive, negative, and neutral. According to Bandi and Fellah [4], TextBlob can indicate a sentence's attitude by calculating the score as a polarity [-1 to 1]. When the polarity of a tweet is less than −0.4, its sentiment is regarded as negative.…”
Section: A Covidsenti Data Collection and Labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed a python loop on all rows in our datasets, and the polarity and subjectivity were returned through the textblob() call. A polarity score is a floating number between 0 and 1, while its subjectivity lies between 0 and 1 [25]. In this study, we are interested in the polarity score, converted to a label, as shown in Equation 2.…”
Section: ) Textblobmentioning
confidence: 99%
“…Naseem et al (1) divided the COVIDSenti dataset into three parts for evaluation and generalization purposes: COVIDSenti_A, COVIDSenti_B, and COVIDSenti_C, which have three sentiments, positive, negative, and neutral for classification purposes. They labeled tweets as positive, negative, and neutral by following the Fellah and Bandi guidelines (35). The COVIDSenti dataset consists of two months of tweets fetch from Twitter using Tweepy, Python Twitter API library.…”
Section: Dataset Selectionmentioning
confidence: 99%